THE POSTULATE OF AFFECTIVE NEUTRALITY VS. VERBAL EXPRESSIVENESS IN THE LEGISLATIVE TEXTS ON GERMAN AND POLISH CRIMINAL LAW. A COMPARATIVE STUDY - KĘSICKA, Karolina (Comparative Legilinguistics, 2015)
The succinct and neutral style of discourse and the abstractiveness of legal terms are the ways to reaching the objectivity by the legal language. It remains at the same time an instrument to express the authority-obedience-relationship. We expect the legal language as a language for special purposes to be aesthetic, expressive and moral neutral. However it seems to be not as much neutral as expected. It contains subjective and expressive elements in the form of emotionally marked terminology, using of emphasis or vague terms and phrases. In this paper I shall illuminate the phenomenon of expressiveness in the language of law based on empirically examining of the selected terminology from the German and Polish Criminal Code. Our purpose is to show the variety of measures for the verbalisation of expressiviness in the analyzed legal texts, to clarify their text function, to research how the examined German and Polish legal terms differ in terms of the degree of expressive intensity and to outline the issues of translation of verbal expression. Finally, our focus is on showing of subjective elements in the process of translation itself such as aestheticization of translation and translators individual decision how far to emphasize the expressive component in the translation.